Thomas Reid, the Internalist - Robert Weston Siscoe (Journal of Modern Philosophy)
Philosophical orthodoxy holds that Thomas Reid is an externalist concerning epistemic justification, characterizing Reid as holding the key to an externalist response to internalism. These externalist accounts of Reid, however, have neglected his work on prejudice, a heretofore unexamined aspect of his epistemology. Reid’s work on prejudice reveals that he is far from an externalist. Despite the views Reid may have inspired, he exemplifies internalism in opting for an accessibility account of justification. For Reid, there are two normative statuses that a belief might satisfy, being blameless and having a just ground. Through reflection, a rational agent is capable of satisfying both of these statuses, making Reid an accessibility internalist about epistemic justification.